2021
DOI: 10.2147/idr.s315367
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Spectrum and Resistance Pattern of Bloodstream Infections Isolated from Postpartum Women: A Multicenter Retrospective Study

Abstract: Purpose Bloodstream infections (BSIs) cause morbidity and mortality in postpartum patients, resulting in poor prognosis for both mother and neonate. Gram-negative bacteremia is a public health threat, with high mortality among vulnerable populations and significant global economic costs. Gram-negative bacteremia and antimicrobial resistance are increasing. This study retrospectively analyzed the pathogen distribution and drug sensitivity among postpartum patients with BSIs to identify appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…In our study, there were only six cases of maternal bacteremia caused by anaerobic bacteria, five of which were identified as Bacteroides fragilis and the remaining one as Clostridium species. The proportion of anaerobic bacteria was lower than that reported in other studies ( Blanco et al, 1981 ; Surgers et al, 2013 ; Zou et al, 2021 ). The detailed reason for the lower rate of anaerobic bacteria is unclear, although different patient composition and hygiene levels and different antibacterial drug exposure levels may be part of the reason.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In our study, there were only six cases of maternal bacteremia caused by anaerobic bacteria, five of which were identified as Bacteroides fragilis and the remaining one as Clostridium species. The proportion of anaerobic bacteria was lower than that reported in other studies ( Blanco et al, 1981 ; Surgers et al, 2013 ; Zou et al, 2021 ). The detailed reason for the lower rate of anaerobic bacteria is unclear, although different patient composition and hygiene levels and different antibacterial drug exposure levels may be part of the reason.…”
Section: Discussioncontrasting
confidence: 69%
“…Bloodstream infection in pregnancy or during the perinatal period is still a significant clinical problem with high morbidity and mortality, even in developed countries ( Waterstone et al, 2001 ; Surgers et al, 2013 ; Zou et al, 2021 ). There are some studies focusing on maternal infectious diseases in mainland China ( Lin et al, 2021 ; Zou et al, 2021 ; Zhong et al, 2022 ) but only one published study focused on perinatal BSI could be found ( Zou et al, 2021 ). Very little is known about various aspects of maternal bacteremia in relation to changes of microbiological epidemiology and obstetric outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The duration of the late phase depends on the recovery of muscle tone and connective tissue in the postpartum period. Physiological changes that occur in the late phase are, as a rule, very gradual and barely noticeable: increased elasticity of ligaments, which can persist for 4-5 months after childbirth; risk of thromboembolism due to increased blood coagulation factors; length and separation of rectus abdominis muscles -diastasis; weakened pelvic floor muscles, including weakened perineal muscles, muscle abnormalities and weakness of the levator anus muscle; enuresis; prolapse of pelvic organs; pelvic floor neuropathy; fecal incontinence and flatulence; swelling of the extremities -hands, feet and ankles; excessive weight gain; lower back pain [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The postpartum period is characterized by a wide range of new states of women's life and increased sensitivity to external factors. The whole range of postnatal changes can be considered as an integrative combination of psychological, physiological and endocrine factors [14,16,17] that affect the physical and mental activity of women, as well as determine their relationship with the child.…”
Section: Introductionmentioning
confidence: 99%
“…Однак ця точка зору не враховує той факт, що КР є хірургічною процедурою з численними потенційними ускладненнями як для матері, так і для дитини. Крім інтраопераційних ризиків (наприклад, інфекція, пошкодження органів або потреба в переливанні крові [39,40]), багато побічних ефектів можуть виникнути після пологів: наприклад, тромбоемболічні ускладнення [41]. Зокрема, існують ускладнення, пов'язані з пізніми вагітностями: розрив матки, безпліддя або аномалії плаценти, такі як передлежання, врощення та пророщення плаценти [42,43,44].…”
unclassified